Downhole circulating cooling device. Issue 1 (April 2021) - Xu, Gao; Jing, Zhou; Haiming, Xie; Haiyan, Shang
Abstract: This paper presents a kind of downhole circulating cooling device in high temperature environment. The device consists of the following components: compressor, condenser, expansion valve, and heat exchanger. The heat exchanger consists of an inner chamber located around the instrument to be cooled and an outer chamber located around the inner chamber. As the cooling fluid passes through the inner chamber, it absorbs heat from the instrument, and then the cooling fluid enters the outer chamber to absorb heat from the wellbore. After absorbing heat, the cooling liquid can be pressurized by the compressor, condensed by the condenser, and then selectively released back to the inner chamber after cooling by the expansion valve, so as to realize the continuous circulation cooling device, so as to realize the thermal insulation and cooling of the instrument. This paper provides an efficient, recyclable and time-saving method for temperature reduction in underground high-temperature environment.